2013
DOI: 10.1089/bfm.2013.9999
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Support for Mothers in Workplace Employment or Educational Settings: Summary Statement

Abstract: The Academy of Breastfeeding Medicine is a worldwide organization of physicians dedicated to the promotion, protection, and support of breastfeeding and human lactation. Our mission is to unite into one association members of the various medical specialties with this common purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 53 publications
0
37
1
6
Order By: Relevance
“…There was no significant relationship between social support and breastfeeding performance. However, the results of another study showed that husbands, mothers, close family members, friends, medical staff, colleagues, and the community can support women to increase their breastfeeding self‐efficacy (Marinelli et al, ). An Australian study showed that women with social support had high breastfeeding self‐efficacy (Blyth et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant relationship between social support and breastfeeding performance. However, the results of another study showed that husbands, mothers, close family members, friends, medical staff, colleagues, and the community can support women to increase their breastfeeding self‐efficacy (Marinelli et al, ). An Australian study showed that women with social support had high breastfeeding self‐efficacy (Blyth et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work suggests workplace support in the form of establishing pumping and storing stations, 45 break-time protection, 121 and flexible work schedules 62,122,123 as critical supports for breastfeeding mothers. 124 Targeting employmentbased factors is particularly important because African American mothers experience shorter maternity leave time on average 21 and commonly return to inflexible work environments after giving birth, 125 and most importantly because return to work postpartum may serve as one of the sources of stress and role overload. 126,127 Providing psychological and social support.…”
Section: Remaining Gapsmentioning
confidence: 99%
“…8 The Academy of Breastfeeding Medicine's position regarding breastfeeding states ''breastfeeding is both a woman's and a child's right, it is therefore the responsibility of the healthcare system, the media, business and marketing sectors, government, and society in general to support and enable each women to fulfill her breastfeeding goals and to eliminate obstacles and constraints to initiating and sustaining optimal breastfeeding practices.'' 13 In order to reach the Healthy People 2020 goals of 60.6% of babies receiving breastmilk at 6 months, 4 support and regulations will need to be established to help support the working, traveling breast-pumping mother. Breastfeeding women are protected under Title VII of the Civil Rights Act of 1964 (as amended by the Pregnancy Discrimination Act of 1978) according to a recent ruling on May 31, 2013 by the United States Court of Appeals for the Fifth Circuit.…”
Section: Discussionmentioning
confidence: 99%